External And Internal Conflict As Revealed In Ernest Hemingway’s The Old Man And The Sea - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is intended to reveal internal and external conflict in Ernest Hemingway’s The Old Man and the Sea. This is qualitative research, in which the data are in the form of words rather than numbers. The information was gathered from the novel The Old Man and the Sea, which served as the primary source, as well as other books on the subject. The result shows that the external conflict is between the old man, Santiago, and society. First, when the other fishermen and society mock the old man, Second, when the old man, Santiago, is struggling against the wild nature, the cruel sea, and the marlin and sharks, in struggling against the mockery, the old man just keeps silent and goes on fishing. The morning cold will easily make the old man sick or unable to hold out. Nonetheless, the old man is always confident in his ability to persevere. The internal conflict begins when the old man, Santiago, feels lonely; he has no wife and no children. Second, he feels disappointed and ashamed. The old man has gone fishing for 84 days, but when he goes home from fishing, he brings only the skeleton. He caught fish, but the shark is the only one. Despite his disappointment, Santiago is a man who is undefeated.